2002
DOI: 10.1159/000057873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amine Fluoride Toothpaste and Gel in High Risk Groups of Hungarian Adolescents: Results of a Longitudinal Study

Abstract: The aim of the study was to establish a preventive program with the combined use of amine fluoride toothpaste and gel in groups of adolescents living in different locations in Hungary. Caries and oral hygiene examinations were performed at the beginning of the study and repeated after 1 and 2 years. The adolescents were divided into 3 groups: 1 control and 2 test groups. The control group continued its usual oral care habits. One of the test groups received Elmex toothpaste for unsupervised home use daily and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The regular use of fl uoridated salt and above all fl uoride gel had a protective effect. This seems reasonable, as a number of studies have confi rmed the properties of fl uoridated salt [Fabien et al, 1996;Macpherson and Stephen, 2001] and fl uoride gel [Attin et al, 1999;Madlena et al, 2002] in caries prevention.…”
Section: Discussionmentioning
confidence: 79%
“…The regular use of fl uoridated salt and above all fl uoride gel had a protective effect. This seems reasonable, as a number of studies have confi rmed the properties of fl uoridated salt [Fabien et al, 1996;Macpherson and Stephen, 2001] and fl uoride gel [Attin et al, 1999;Madlena et al, 2002] in caries prevention.…”
Section: Discussionmentioning
confidence: 79%
“…It was scheduled for two years with the combined use of amine fluoride toothpaste and gel in 14-16 year old adolescents. On the basis of a previous assessment of their oral hygiene and dental status, they were considered as a high risk group (17). The results showed that combined use of products containing fluoride (toothpaste twice a day, and gel once a week) resulted in better caries reduction, improvement of oral…”
Section: Elmex Products Contain Amine Fluoride Besides Its Fluoride mentioning
confidence: 99%
“…hygiene and a remineralization effect than use of toothpaste alone (17,18). Regarding the results, significant differences could be found between the groups using toothpaste and gel together compared with the groups using toothpaste only (p<0.05).…”
Section: Fig 3 Caries Increment In Dmft and Dmfs Values (Mean±sd) mentioning
confidence: 99%
“…Another longitudinal study was performed showing the beneficial effect of toothpaste and gel containing AmF in high risk groups of adolescents (14). The study consisted of two parts.…”
Section: Studies In High Risk Groupsmentioning
confidence: 99%